PSYCHOLOGICAL ANALYSIS OF PARADIGMS OF DEVELOPMENT OF MODERN HIGHER EDUCATION - Radchuk, Halyna; Adamska, Zoriana; Chopyk, Solomiia; Sviderska, Halyna; Oleksiuk, Viktoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article presents a theoretical and methodological analysis of modern educational paradigms and presents axiological vectors of higher education development. The authors identify four basic educational paradigms: cognitive informational, personal (humanistic), competence based and cultural (humanitarian). It has been found that, unlike instrument-oriented learning, which provides the translation, reproduction and assimilation of knowledge, skills, technologies (cognitive informational and competence paradigms) and therefore is secondary to the processes of personality development, education should firstly be focused on development of a holistic personality, ensuring its nature and uniqueness (personal and cultural paradigms). It has been proven that at the theoretical level there has been a drastic narrowing of the semantic field of scientific and pedagogical reflection: the focus is on the production of the amount of knowledge, programmed social behaviour, technologies of activity of the future specialists. It has been shown that higher education institutions are more and more inclined to provide pragmatic education, and training professionals-functionaries. It is determined that the reform of modern education should be based on the idea of integrity, which actualises the problem of careful reflexive and methodological support of the modern higher education system and the development of specific humanitarian educational technologies.